Disaster Prone Area Entrepreneurs: The Importance of Entrepreneurial Experience and Entrepreneurial Passion for Entrepreneurial Resilience - Emrizal, Emrizal; Primadona, Primadona (Budapest International Research and Critics University, 2022)
Research on entrepreneurial resilience has recently been growing but no quantitative investigation has been presented for examining factors that contribute in its improvement. This study was intended to examine the influence of entrepreneurial experience and entrepreneurial passion upon entrepreneurial resilience. This quantitative research was performed on Small and Medium Enterprises in culinary in disaster prone area of West Sumatera. The quantitative technique of Structural Equation Modelling was used with a number of samples of 382 entrepreneurs. The result indicates a positive and significant correlation between entrepreneurial experience and entrepreneurial resilience. Similar result was also found in the correlation between entrepreneurial passion and entrepreneurial resilience. Consequently, this research contributes a theoretical proposition that entrepreneurial experience and entrepreneurial passion play significant roles in establishing entrepreneurial resilience. The study can also help entrepreneurs in comprehending the importance of entrepreneurial passion and experience in order to become resilient. The government can also be informed of the importance of both entrepreneurial aspects so that public policies and executive decision they make to provide continuous supports for entrepreneurs can be comprehensively based on valid scientific consideration and result in entrepreneurs’ resilience in dealing with difficult period and business uncertainty.